2021
DOI: 10.4314/jasem.v25i5.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Forest Investment, Financial Flows and Revenue Collection in the Abia State Forest Sector, Nigeria

Abstract: Varieties of resources abound in the forests of Nigeria and especially in Abia state, an economic treasure house of resources. Sustainable management of the forests in Nigeria is crucial for a consistent supply of forest resources. Ten forest reserves were surveyed to determine the extent of the government’s involvement in sustainable forest management in Abia State. The government consider the forest reserves, as a revenue-generating venture, leading to the excessive exploitation of forest resources in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Sustainable forest management is the use of forests and forest lands in a way, and at a rate, that maintains their biodiversity, productivity, regeneration capacity, vitality, and their potential to fulfill, now and in the future, relevant ecological, economic and social functions, at local, national, and global levels, and without causing damage to other ecosystems [3]. The sustainable management of the forests in Nigeria is crucial for a consistent supply of forest resources for the present and posterity [4]. Varieties of resources abound in the forests of Nigeria and especially in Abia State and they include soil and its mineral deposits, water sources, rock, outcrops, rare landscapes and, in the biological sense, plant and animals in all their various forms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustainable forest management is the use of forests and forest lands in a way, and at a rate, that maintains their biodiversity, productivity, regeneration capacity, vitality, and their potential to fulfill, now and in the future, relevant ecological, economic and social functions, at local, national, and global levels, and without causing damage to other ecosystems [3]. The sustainable management of the forests in Nigeria is crucial for a consistent supply of forest resources for the present and posterity [4]. Varieties of resources abound in the forests of Nigeria and especially in Abia State and they include soil and its mineral deposits, water sources, rock, outcrops, rare landscapes and, in the biological sense, plant and animals in all their various forms.…”
Section: Introductionmentioning
confidence: 99%
“…Egu et al [4], recently reported some approaches for forest management adopted by the Abia State government in managing State forest reserves which present the need and pathway to potential investment and studies on financial flows. Abia State has 19 forest reserves comprising of four (4) are natural forest reserves and fifteen (15) plantation forest reserves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation